ESTETIKA BUNYI PANTUN DALAM LOMBA BERBALAS PANTUN TINGKAT SMA/MA SEDERAJAT PRAKTIKUM SASTRA KE-25 UNIVERSITAS RIAU - Mirnanda Mirnanda; Elmustian Elmustian; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study discusses the Aesthetics Sound Poem in reciprocate Poem Competition equal Level senior high school/MA Praktikum Sastra Ke-25 University of Riau. The problem in this study is what aesthetics sound poem in poem who will be delivered by reciprocated poem competition participant. This study was aimed to describe what are the shapes of aesthetics sound in poem who will be delivered by reciprocated poem competition participant, district consisting of rhythm (metrum and rhythm), efoni, kakafoni, anaphora, epistrophe, alliteration, assonance, and onomatopoeic. This study benefit is theoretical, practical and educational useful for readers. The theory used in this study is the theory presented by Hasanuddin WS. The time of this research started in March 2017 to November 2017. This type of research is qualitative research. The method used in this research is descriptive qualitative method approach. The data in this study is poems who will be delivered by reciprocated poem competition participant equal level Senior high school/MA in reciprocate poem competition event by the Student Association of Educational Studies Program Language and Literature Indonesia Riau University submitted. The technique for collecting data in this study is the use of the recording technique and the validity of the data is obtained by using data triangulation technique. Based on research results,the authors found (55 data of the first phoetic, 64 data of the middle phoetic, 152 data of the last phoeti, and 55 data of the phoetic), 152 data of ephoni, 150 data of cacaphony, 29 data of anaphora, 7 data of ephyphora, 152 data of aliteration, 121 data of assonance, 3 data of onomathope. The results of this study indicate that the poems who will be delivered by reciprocate poem competition participant full of aesthetics sound, this is proved by full of aesthetics sound in poems who will be delivered by competition participant.Keyword : Aesthetics sound, poems, reciprocated poem competition